2013
DOI: 10.1093/rpd/nct071
|View full text |Cite
|
Sign up to set email alerts
|

Natural radioactivity levels in lake sediment samples

Abstract: The radioactivity concentrations of nuclides (238)U, (232)Th and (40)K in lake sediments collected from 15 different stations at Altınkaya dam lake and 12 different stations at Derbent dam lake in Turkey were measured using high-resolution gamma-ray spectrometry. The measurement was done using a coaxial HPGe detector system coupled to the Ortec-Dspect jr digital MCA system. The average measured activity concentrations of the nuclides (238)U, (232)Th and (40)K were found to be 19.5, 27.7 and 460 Bq kg(-1) in Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
0
4
2
Order By: Relevance
“…The activity concentrations of 226 Moreover, the comparison of mean activity concentrations of the present study with published results in sediment samples is shown in Table 3. The 226 Ra activity concentrations reported in the Van Lake [1], the Metiterranean Central Basin [19], the Altınkaya Dam Lake [8], the Derbent Dam Lake [8], the Kızılırmak Delta [11] and the Yangtze Estuary [20] are higher than our values, but those for the Deriner, Borçka and Muratlı Dam Lakes [10] and the Vaigai River [21] are not.…”
Section: Natural Radioactivity In Sedimentcontrasting
confidence: 80%
See 2 more Smart Citations
“…The activity concentrations of 226 Moreover, the comparison of mean activity concentrations of the present study with published results in sediment samples is shown in Table 3. The 226 Ra activity concentrations reported in the Van Lake [1], the Metiterranean Central Basin [19], the Altınkaya Dam Lake [8], the Derbent Dam Lake [8], the Kızılırmak Delta [11] and the Yangtze Estuary [20] are higher than our values, but those for the Deriner, Borçka and Muratlı Dam Lakes [10] and the Vaigai River [21] are not.…”
Section: Natural Radioactivity In Sedimentcontrasting
confidence: 80%
“…In addition, radionuclides accumulating in the lake contaminate the water environment in which they are in contact. Dam waters are frequently used to irrigate agricultural lands located in the nearby area and therefore the determination of radioactive pollution in sediment samples in lake environment shows the importance of this research study [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge of radionuclides distributions in the sediments acts an essential part in monitoring of environmental contamination and assessment of radiological hazard arising from natural sources. For this purpose, in the recent years many studies give an importance to the measurements of the activity concentrations of natural radionuclides and their hazard on human health [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These granitoids have high Lu/Hf ratios of 0.07 to 0.11, i.e. similar to those of meta-sedimentary rocks, 0.09 to 0.11 (Eroğlu et al, 2013), suggesting the participation of sediments. The crustal extension could involve sediments into magma generation, and change the proportion of Hf and Nd isotopes in the melt.…”
Section: Nd-hf Isotope Decouplingmentioning
confidence: 77%